Effect of Omega-3 Supplementation on Lipocalin 2 and Retinol-Binding Protein 4 in Type 2 Diabetic Patients - FARAHBAKHSH-FARSI, Payam (Iran J Public Health, 2016)
BACKGROUND: Serum levels of lipocalin 2 (LCN 2) and retinol-binding protein-4 (RBP 4), increase in type 2 diabetes mellitus (T2DM). We sought to determine whether serum LCN 2 and RBP 4 change after an intervention with omega-3 fatty acids supplementation in diabetic patients. METHODS: Forty-five type 2 diabetic patients from Iranian Diabetic Association in Tehran, Iran in 2013 were randomly recruited into two groups: one group received 4 g/d omega-3 for 10 wk; and the control group received placebo. Blood samples, food intake records, anthropometric measurements were obtained from all participants at the beginning and end of the study. RESULTS: Fasting RBP 4 plasma levels significantly changed after 10 wk supplementation (P = 0.01). The LCN 2 concentrations decreased in omega-3 group, but the changes were not statistically significant. Omega-3 supplementation had no noticeable effect on anthropometric factors. CONCLUSION: These findings provide a rationale for omega-3 supplements aimed at lowering serum RBP 4 levels in T2DM.